Criminal Defamation Through Social Media and Its Legal Implications in Indonesia - Herlina, Sri (Scholar Center, 2025)
The digital era has brought about a fundamental transformation in the communication patterns of Indonesian society through social media platforms, while at the same time giving rise to complex challenges in the field of criminal law. The Constitutional Court Decision No. 105/PUU-XXII/2024, issued on April 29, 2025, has shifted the legal paradigm of defamation by restricting the object of the offense solely to individual persons. This study analyzes the evolution of legal regulation of defamation in the digital era, the impact of the Constitutional Court’s decision on freedom of expression, and the challenges in implementing Law No. 1 of 2024 concerning the Second Amendment to the Electronic Information and Transactions Law (ITE Law) in law enforcement practices. Social media has become a virtual public sphere that can influence the reputation of both individuals and institutions with unlimited speed and reach, thereby requiring adaptive legal regulation (Rumondor et al., 2024). This research employs a normative juridical method with a statutory approach and judicial decision analysis. The analysis shows that although the Constitutional Court’s decision provides broader space for criticism of public institutions, technical challenges and legal harmonization still require regulatory strengthening and capacity-building for law enforcement officials. This study recommends the necessity of comprehensive dissemination to law enforcement authorities, the development of standardized operational procedures, and the enhancement of digital literacy among the public to prevent criminal defamation through social media.